The Effect Of The (T.T.W) Strategy On Expressive Performance And The Development Of Creative Thinking Among Fourth-Year Literary Students (Journal of the College of Basic Education, 2026)
The research aims to identify (the effect of the (T.T.W) strategy on expressive performance and the development of creative thinking among fourth-grade literary students), and the researcher followed the experimental method as it is the appropriate and suitable method for the nature and goal of the research, and she chose one of the designs with partial control, which is the design of the experimental and control group, random selection withFor the post-test, the researcher intentionally chose a research sample consisting of (60) female students from secondary school (Al-Sirra) and middle school (Abeer Iraq) affiliated with the General Directorate of Education of Al-Aziziyah in Wasit Governorate, with (30) female students in the experimental group and (30) female students in the control group. The searcher was rewarded between the two research groups inThe variables are chronological age lculated in months, parents’ academic achievement, Arabic language scores for the academic year 2024/2025 (for the third intermediate grade), intelligence test scores, and pre-creative thinking test scores, The researcher studied the two research groups herself, the experimental group according to the (T.T.W) strategy, and the control group using the traditional method, and the teaching period lasted (8) weeks. The researcher prepared a test to measure expressive performance, through a questionnaire consisting of (3) topics after presenting it to the group of arbitrators, the Arabic language and its teaching methods. To choose a topic that would test the two research groups, then I corrected the test based on the criteria for correcting Al-Hallaq (2007), and then I relied on the “Torrance” scale to measure their creative thinking, then I corrected the scale according to the criteria of the same scale, as the two tests were completed at the end of the experiment, and the data and results were processed statistically using the (SPSS) program, and the research resultedAbout the following result:“There is a statistically significant difference, at a significance level (0.05), between the average scores of the female students in the experimental group and the average scores of the female students in the control group, in favor of the experimental group in the two tests of expressive and creative thinking.”